Associations between estradiol and hyperuricemia and the mediating effects of TC, TG, and TyG: NHANES 2013–2016 - Zhang, Chuxin; Qian, Hongyang; Cui, Yiwei; Li, Xiaojuan; Cheng, Yuli; Gao, Lin (Frontiers in Endocrinology, 2024)
Objectives: To explore the relationship between estradiol (E2) and the incidence of hyperuricemia (HUA) in adult women and to explore whether glucolipid metabolism disorders play a mediating role in mediating this relationship.Methods: A total of 2941 participants aged 20-65 years were included in the National Health and Nutrition Examination Survey (NHANES) 2013-2016. Multivariate logistic regression analysis was performed to evaluate the correlations of E2 with HUA. Multivariate linear regression analysis was performed to evaluate the associations between E2 and triglyceride (TG), total cholesterol (TC), and the triglyceride-glucose index (TyG). The restricted cubic spline (RCS) model was used to further explore the association between E2 and HUA and between TG, TC, and TyG and HUA. Mediation analyses were performed to examine whether TC, TG, and TyG mediated the relationship between E2 and HUA.Results: After adjusting for covariates, logistic regression revealed that ln(E2) was significantly associated with HUA in the female subgroup (p=0.035) and that the incidence of HUA tended to increase with decreasing ln(E2) (p for trend=0.026).Linear regression showed that E2 was significantly associated with TC (p=0.032), TG (p=0.019), and TyG (p=0.048). The RCS model showed that ln(E2) was linearly correlated with the incidence of . TC and TyG were linearly correlated with HUA (TC: p-overall=0.0039, p-nonlinear= 0.4774; TyG: p-overall=0.0082, p-nonlinear=0.0663), while TG was nonlinearly correlated with HUA. Mediation analyses revealed that TC, TG, and TyG significantly mediated the relationship between ln(E2) and HUA (TC, indirect effect: -0.00148, 7.5%, p=0.008; TG, indirect effect: -0.00062, 3.1%, p=0.004; TyG, indirect effect: -0.00113, 5.6%, p=0.016).In conclusion, this study demonstrated that compared to women aged 20-45 years, women aged 45-55 years and 55-65 years had lower E2 levels and a greater incidence of HUA. E2 levels and the incidence of HUA were negatively associated in female individuals but not in male individuals. In addition, TC, TG, and TyG, which are markers of glucolipid metabolism, played a mediating role in the association between E2 and HUA.